Targeting Coronaviral Replication and Cellular JAK2 Mediated Dominant NF-κB Activation for Comprehensive and Ultimate Inhibition of Coronaviral Activity - Cheng-Wei Yang (Nature Portfolio, 2017)
Abstract Tylophorine-based compounds exert broad spectral, potent inhibition of coronaviruses. NF-κB activation is a common pro-inflammatory response of host cells to viral infection. The aims of this study were to (i) find an effective combination treatment for coronaviral infections through targeting of the virus per se and cellular NF-κB activity; and (ii) to study the underling mechanisms. We found that tylophorine-based compounds target the TGEV viral RNA and effectively inhibit TGEV replication. NF-κB inhibition also leads to anti-TGEV replication. NF-κB activation induced by TGEV infection was found to be associated with two convergent pathways, IKK-2_IκBα/p65 and JAK2 mediated p65 phosphorylation, in swine testicular cells. JAK2 inhibition either by CYT387 (a JAK family inhibitor) or by silencing JAK2-expression revealed a dominant JAK2 mediated p65 phosphorylation pathway for NF-κB activation and resulted in NF-κB inhibition, which overrode the IκBα regulation via the IKK-2. Finally, tylophorine-based compounds work cooperatively with CYT387 to impart comprehensive anti-TGEV activities. The combination treatment, wherein a tylophorine compound targets TGEV and a JAK2 inhibitor blocks the alternative dominant NF-κB activation mediated by JAK2, is more effective and comprehensive than either one alone and constitutes a feasible approach for the treatment of SARS-CoV or MERS-CoV.